Vegetation Change Detection of Khagrachhari Sadar Upazila Using GIS and Remote Sensing - Latifa, GA; Marma, S; Islam, M (Journal of Biodiversity Conservation and Bioresource Management, 2023)
The change of vegetation in Khagrachhari Sadar Upazila during 1991 to 2021 was investigated taking data in 10 years intervals. Satellite images of Landsat 4-5 TM (30 October 1991, 19 March 2001 and 11 February 2011) and Landsat 8 OLI/TIRS (6 February 2021) from USGS Earth Explorer have been extracted. Image classification, analyzing and visualizing the data was accomplished by ArcGIS 10.7.1 software and Microsoft excel. In 1991, vegetation coverage (Forest and agriculture) and non-vegetated area (water body, bare land) were 161.15 km2 (61.19%) and 99.17 km2 (38.09%), respectively. After 10 years (in 2001) vegetation coverage slightly increased (by 0.83%) resulting a little decrease in nonvegetated area. The area became 184.63 km2 (62.60%) and 97.28 km2 (37.40%), respectively for vegetated and non-vegetated coverage. However, since 2011 a decreasing trend for vegetation coverage was observed, 161.81 km2 (62.2%) in 2011 which decreased to 157.97 km2 (60.72%) in 2021. Consequently non-vegetated area increased from 98.34 km2 (37.80%) to 102.18 km2 (39.28%) in this period. The overall loss of 3.18 km2 of vegetation over the last 30 years was mainly due to rapid growth of population and encroachment of hilly area for settlement. This loss of vegetation coverage is affecting the ecological balance of the hilly areas of Bangladesh. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(2): 103-108